2003
DOI: 10.1002/jmor.10112
|View full text |Cite
|
Sign up to set email alerts
|

Pericardium of the frog, Rana esculenta, is morphologically designed as a lymphatic space

Abstract: The importance of the pericardium and the pericardial fluid (PF) in the control of cardiac function has emerged over the past few years. Despite the acknowledgment that amphibians are exposed to both dehydration and excessive water accumulation, nothing is known about their pericardial structure and the morphological basis of the PF formation. We have studied the parietal pericardium (PP) morphology in Rana esculenta by electron microscopy. SEM images of the inner surface, which lines the pericardial cavity, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The pericardial space is a large lymphatic sac, and the composition of the pericardial fluid is influenced by the myocardial interstitial fluid (16). Laham et al (17) reported that intrapericardial delivery provides markedly higher myocardial deposition and retention than intracoronary or intravenous delivery.…”
Section: Discussionmentioning
confidence: 98%
“…The pericardial space is a large lymphatic sac, and the composition of the pericardial fluid is influenced by the myocardial interstitial fluid (16). Laham et al (17) reported that intrapericardial delivery provides markedly higher myocardial deposition and retention than intracoronary or intravenous delivery.…”
Section: Discussionmentioning
confidence: 98%
“…In birds and, more prominently, in mammals, lymph nodes were added for important functions in acquired immunity. Although the zebrafish model provides an extremely valuable experimental tool for research into the development of the blood vascular system, there is no well-defined lymphatic system in zebrafish, and Xenopus (frogs) have long served as an excellent experimental model for studies of the development and function of the lymphatic vascular system (Day et al, 1963;Koyama and Horimoto, 1988;Greber and Schipp, 1990;Baldwin et al, 1993;Ohtani et al, 2001;Cerra et al, 2003). In this review, we will discuss several genes that recently have been found to play essential roles in early mammalian lymphatic development and in lymphatic function, with particular attention to mutant phenotypes in mice and humans.…”
Section: Historic and Phylogenetic Perspectives Of Lymphatic Vessel Dmentioning
confidence: 99%